NILAI-NILAI PENDIDIKAN AKHLAK DALAM KITAB AL-ARBA’IN AL-NAWAWIYAH KARYA IMAM NAWAWI - B, Muhammad Rusmin; Al Qifari, Abudzar (Universitas Islam Negeri Alauddin Makassar, 2023)
This study discusses the values of moral education in the book al-Arba'in al-Nawawiyah by Imam Nawawi. This research was conducted with the objectives: (1) to determine the values of moral education contained in the Kitab al-Arba'in al-Nawawiyah, (2) to determine the concept of implementing the values of moral education in the Kitab al-Arba'in al-Nawawiyah. Nawawiyah. This library research research is carried out by collecting data or materials related to the theme of the discussion and the problem, which is taken from library sources, then analyzed by the method of content analysis, this analysis examines the values of moral education from the contents of the book al-Arba'in al-Nawawiyah. To support this research, the author uses the main data source, namely, the book of hadith al-Arba'in al-Nawawiyah by Imam Nawawi. Data were analyzed using content analysis. The results of the study show that the book al-Arba'in al-Nawawiyah contains the values of moral education, broadly divided into two parts, namely: morals to Allah Swt and morals to creatures. First, Morals towards Allah include: monotheism, piety, prayer, shame, and trustworthiness, second, Morals towards creatures include: morality towards fellow humans (saying good, being generous, holding back anger, maintaining honor, advice, brotherhood, helper, forgiving), morals towards oneself (maintaining cleanliness and beauty and asceticism), morals towards neighbors and guests, morals towards animals. Some of these educational values can be implemented in schools and in everyday life by using several methods including the mau'izah (advice) method, the uswatuh hasanah (exemplary) method, the ta'wid method (habituation) and the targhib and tarhib methods.